Ekoturystyczne gospodarstwa w obszarach przyrodniczo cennych - na przykładzie Polski - Zielińska, Anetta (Eco-tourism on the nature preserved areas according - to polish standards, 2005)
There is a valuable potential on the nature preserved areas for the development according to eco-development principles, which does not cause any harm to the nature quality. The economic development on the nature preserved areas can be accomplished in the ecoeconomic way, for instance ecotourism, which should be an active form of nature protection. The localization of ecotourist farms should be positively correlated with the nature preserved areas.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1095, s. 209-216